Membrane fusion and syncytial neuronal cytoplasmic connection - Sotnikov, O. S. (Oleg Semenovich); Laktionova, A.A (Foundations of material science and engineering, 2016)
In this monograph, for the first time, results of systematic studies of cytoplasmic syncytial connections in the vertebrate and invertebrate nervous system are presented. This book is of interest to neurophysiologists, neuromorphologists, and neuropathologists, as well as to lecturers in the corresponding general courses about the neuron.